Strengthening extension research in animal husbandry: review of issues and strategies - PONNUSAMY, K; PACHAIYAPPAN, K (The Indian Journal of Animal Sciences, 2018)
The crucial role played by animal husbandry extension resulted in 8.5 times increase in milk production, 43 times in egg production and 13 times in fish production since 1950s in India. However, extension especially its research component is often criticized for its inability to respond to changing ground realities in production and socio-economic scenario. Several studies, deliberations in seminars and conferences and viewpoints of experts and policy makers often emphasise the reorientation of extension research from diffusion and communication dimension to more of action oriented experimental studies keeping in view emerging areas of research like skill building, sustainability, climate change, commercialization, impact assessment, value addition and entrepreneurship. The strategies that could facilitate the reorientation include capacitation of extension faculties and students on advanced methodologies and statistical techniques, minimizing operational difficulties, networking and coordinated research, inculcating ethics and professional excellence and sensitization of extension researchers at their work place.